Paper-based Analytical Devices with Integrated VLSI Potentiostat - Punjiya, Meera. (2017)
Abstract: There is a need for low cost, self-contained, point-of-care medical diagnostics for resource poor settings. Such diagnostics have the potential to greatly improve health outcomes through early detection and rapid diagnosis. Recently, paper based devices similar to paper strips in glucose meters have been demonstrated as a viable and low cost platform for diagnostics. In addition to being low cost, paper is easily transportable, biocompatible and can be safely disposed by incineration. Furthermore these paper-based sensors can be fabricated at room temperature using readily available and inexpensive equipment and materials, essential in regions with limited resources. Paper based devices which employ electrochemical sensing methods are the most sensitive class of these devices. Unfortunately, readout is traditionally completed with a benchtop potentiostat not suitable for portable applications. This thesis presents a CMOS readout IC with a VLSI potentiostat designed for sensing with paper-based electrochemical biosensors and a 3D electrochemical paper based analytical device suitable for multi-analyte detection. The platform is evaluated for dopamine and glucose sensing. Collectively, this work contributes to a portable low-cost diagnostics platform for use in resource scarce areas.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Electrical Engineering.; Advisor: Sameer Sonkusale.; Committee: Valencia Koomson, and Xiaocheng Jiang.; Keyword: Electrical engineering.